HOW FINTECH CONDITIONS IN INDONESIA DURING THE COVID-19 PANDEMIC? - Nasution, Lia Nazliana; Ramli, Ramli; Sadalia, Isfenti (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
This study aims to see how the FinTech financial services industry's condition during the COVID-19 pandemic in Indonesia in a quantitative descriptive manner. E-money transactions, ATM/debit cards, credit cards, turnaround clearing, and RTGS transactions focus on our observations. Limited mobility during the COVID-19 pandemic and the large-scale social restrictions (PSBB) policy has increased electronic money payment transactions. In contrast to clearing turnover and RTGS transactions, they showed a downward trend; however, since the 'new normal' began in June, turnover in clearing and RTGS transactions improved.